First molecular evidence of Clostridium perfringens in adult Fasciola spp. isolates in cattle hosts - Karagulle, Burcu; Celik, Figen; Simsek, Sami; Ahmed, Haroon; Shen, Yujuan; Cao, Jianping (Frontiers Media Sa, 2022)
Fasciolosis is a parasitic disease caused by Fasciola spp. It is a prevalent helminth infection globally. Clostridial hepatitis is a general name refer to disorders caused by a few clostridial agents that most severely affect the liver. Migration of young parasite forms (mostly Fasciola hepatica) in the parenchymal tissue of the liver causes necrosis and anaerobic environment, stimulating the proliferation of C. novyi type B spores. This study investigated the occurrence of Clostridium spp in adult Fasciola spp isolates. Isolates (n = 100) were collected from the bile ducts of infected cattle after slaughter. Total genomic DNA was extracted from each sample. A multiplex-PCR based on the flagellin C (fliC) gene was used for quick identification of C. chauvoei, C. haemolyticum, C. novyi types A and B, and C. septicum. In addition, a pair of primers Cpa (F) and Cpa (R) were used for detection of the C. perfringens alpha toxin gene. The products were sequenced. No band was obtained after multiplex-PCR of the fliC gene. A 247 bp band was detected in two isolates using the Cpa primers. BLAST analysis of these two isolates characterized both as C. perfringens alpha toxin. This is the first description of the molecular detection of C. perfringens in flukes. Further studies are needed to investigate whether Clostridum species is also carried by other developmental forms (egg and larval stages) of Fasciola spp.
Keywords: cattle; Clostridium perfringens; Fasciola spp.; liver; necrotic hepatitis